The effects of structure-soil-structure interaction on seismic response of high-rise buildings equipped with optimized tuned mass damper. (April 2023) - Fatollahpour, Amirhosein; Tafakori, Ehsan; Ali Asghar Arjmandi, Seyyed
Abstract: Nowadays, various vibration control tools and methods are used to improve the behavior of structures. Tuned Mass Damper (TMD) is one of the simplest and most used passive control tools, which consists of a combination of spring, mass, and a damping mechanism. However, some factors, such as the type of soil beneath the structure and the existence of another structure, can affect the damper's performance. This study investigates the effects of Structure-Soil-Structure Interaction (SSSI) on the seismic response of two 20-story steel moment frames equipped with TMD. Assuming an elastic behavior for the soil and plane strain problem, the reduced stiffness matrix of the foundation-soil-foundation system is obtained using static analysis of the 2D finite element method in Abaqus. Then, it is applied to 2D linear models of structures using a combination of springs and a newly developed element in OpenSEES. Furthermore, particle swarm optimization algorithm is used to optimize the design parameters of TMD. The seismic responses are obtained under ten far-field seismic records from the time history analysis. The results reveal that considering SSSI can significantly increase the responses of both structures. Nevertheless, exploiting TMD with optimized parameters in the 20-story structures reduces the seismic responses.